2019
DOI: 10.3390/ma12182984
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fineness on the Hydration Activity Index of Ground Granulated Blast Furnace Slag

Abstract: To improve the properties of ground granulated blast furnace slag (GGBS) and utilize ground granulated blast furnace slag efficiently, this study investigates the effect of fineness on the hydration activity index (HAI) of ground granulated blast furnace slag. The hydration activity index of GGBS with six specific surface areas (SSAs) was characterized by the ratio of compressive strength of the prismatic mortar test block. The particle size distribution of GGBS with different grinding times was tested by lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 29 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…All of them yielded a SF3 slump-flow class SCC. Finally, the use of CEM III/A hindered the uniform dragging of the aggregate particles in the slump-flow test, due to the higher grinding fineness of CEM III/A in comparison with CEM I (Dai et al, 2019). A reduction in the coarse RCA content used in the mixtures allowed solving this problem.…”
Section: Designmentioning
confidence: 99%
“…All of them yielded a SF3 slump-flow class SCC. Finally, the use of CEM III/A hindered the uniform dragging of the aggregate particles in the slump-flow test, due to the higher grinding fineness of CEM III/A in comparison with CEM I (Dai et al, 2019). A reduction in the coarse RCA content used in the mixtures allowed solving this problem.…”
Section: Designmentioning
confidence: 99%
“…The compressive strength of the benchmark mortar at the same age increases with the increase of the specific surface area of GGFBS. The reason is that with the increase of the specific surface area of GGFBS, the proportion of fine particles in GGFBS increases, and the void filling of cement particles is more uniform and effective [76]. Ultrafine steel slag shows high early activity.…”
Section: Mechanical Activationmentioning
confidence: 99%
“…ere has been a lot of studies on using these by-products in concrete. Fly ash (FA), ground granulated blast furnace slag (GGBS), silica fume (SF), rice husk ash (RHA), calcined clay, and other supplementary cementing materials (SCMs) have all been employed as cement substitutes [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…e results showed that increasing the specific surface area of GGBS enhances the splitting tensile strength [14], compressive strength, and hydration activity index [15]. e influence of GGBS on the properties and performance of ultrahigh performance concrete (UHPC) was explored by Ghafari et al [16] and Yalcinkaya and Copuroglu [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation